Country and climate: Journeys toward the decolonial option among non-indigenous climate activists - Bryant, Elise K.; Sonn, Christopher C. (PINS-Psychology in Society, 2022)
Climate and environmental activism have long grappled with concerns of First Nations’ land, rights, and sovereignty in the Australian settler-colonial context. However, analyses of environmental campaigns indicate that there are tensions with the realities of decolonial praxis in the intersubjective exchange among Indigenous and non-Indigenous people. We aimed to respond to and work alongside First Nations’ agendas in this space in by making visible the role of coloniality, interrogating complicity and colonial narcissism, and exploring ways in which non-Indigenous climate activists understand and traverse the decolonial option in order to disrupt hegemonic systems of colonial violence. From the thematic analysis of interviews with five non-Indigenous climate activists from around Australia, four major themes emerged: development of positionality awareness, negotiation of positionality, decolonial imaginings, and a shared journey of (un)learning. These findings illustrate the shifts in subjectivities, the imaginings of decolonial futures, the dilemmas of navigating competing discourses, and the fundamental importance of ongoing learning and unlearning with one another in authentic dialogue. Considerations for future research and decolonial climate activism actions are explored.